CRIMINAL SANCTIONS AGAINST CHILD OFFENDERS REPEAT OFFENSE - Moh. Haizul Ma’aly; Rahmatul Hidayati; Budi Parmono (Pena Cendekia Insani, 2025)
This research focuses on the ambiguity of legal norms related to recidivism in the juvenile justice system in Indonesia, particularly within the framework of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA). This research uses a normative juridical approach with conceptual analysis methods and a statute approach, supported by empirical data from five case studies of recidivist juvenile cases tried at the District Court